The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1158/1055-9965.epi-18-0940
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian Randomization Study for Genetically Predicted Polyunsaturated Fatty Acids Levels on Overall Cancer Risk and Mortality

Abstract: Background: Observational studies evaluating the link between polyunsaturated fatty acids (PUFA) and cancers have yielded mixed findings. We used Mendelian randomization (MR) to evaluate whether genetic evidence supports a causal role for PUFAs on overall cancer outcomes.Methods: We identified genetic instruments for six PUFAs from previous literature and evaluated their association with overall cancer risk (46,155 cases, 270,342 controls) and cancer mortality (6,998 deaths, 270,342 controls) among the UK Biob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 58 publications
0
20
2
Order By: Relevance
“…Our results based on data from UK Biobank and the International Lung Cancer Consortium, FinnGen consortium, and BioBank Japan provide further support for an association between higher AA concentrations and increased risk of lung cancer. As in our study, no association was observed between genetically predicted AA concentrations and risk of breast, prostate, and pancreatic cancer in a previous MR study in UK Biobank participants [25]. We are not aware of any previous study of genetically predicted AA concentrations or FADS1 polymorphisms in relation to esophageal cancer, and MR studies of AA and other cancers are scarce.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Our results based on data from UK Biobank and the International Lung Cancer Consortium, FinnGen consortium, and BioBank Japan provide further support for an association between higher AA concentrations and increased risk of lung cancer. As in our study, no association was observed between genetically predicted AA concentrations and risk of breast, prostate, and pancreatic cancer in a previous MR study in UK Biobank participants [25]. We are not aware of any previous study of genetically predicted AA concentrations or FADS1 polymorphisms in relation to esophageal cancer, and MR studies of AA and other cancers are scarce.…”
Section: Discussioncontrasting
confidence: 61%
“…With regard to lung cancer, a previous study showed that a variant in the FADS1 gene (rs174548) was statistically significantly associated with lung cancer risk in 13,821 Europeans and 18,471 Asians [26]. In addition, genetically predicted AA concentrations (per SD increase) were associated with an OR of lung cancer of 1.08 (95% CI 1.00e1.16) in UK Biobank (1863 lung cancer cases) [25]. Our results based on data from UK Biobank and the International Lung Cancer Consortium, FinnGen consortium, and BioBank Japan provide further support for an association between higher AA concentrations and increased risk of lung cancer.…”
Section: Discussionmentioning
confidence: 98%
“…After excluding duplicate papers (n=5991) and studies that did not meet the inclusion criteria (n=6829), 53 full articles of potentially relevant studies were assessed for eligibility ( fig 1 ). After full text reviews, eight articles were excluded for being conducted on patients who required haemodialysis (n=1) 70 or critically ill patients (n=1), 71 having a case-control design (n=1), 72 assessing genetically predicted ALA levels rather than tissue levels (n=1), 73 and not reporting relative risk estimates (n=1) or 95% confidence intervals (n=3). 74 75 76 In addition, two different publications were found for the Nurses’ Health Study, 34 77 three for the Health Professionals Follow-up Study, 34 78 79 and two for the Cardiovascular Health Study.…”
Section: Resultsmentioning
confidence: 99%
“…. Given 6 individual cancers were considered, we set a significance threshold of 0.004/36=0.0001.” 83 …”
Section: Methodsmentioning
confidence: 99%